A critical analysis of whether the current legislated exit tax provisions of South Africa are proportional to the legitimate purpose of those provisions - Botha, Leandi (Department of Finance and Tax, 2019)
When a South African taxpayer transfers his/her residence to another tax jurisdiction, exit tax is levied on certain accrued gains on the basis that a termination of residency results in a deemed disposal. This creates a fiction that the taxpayer disposes of his/her assets even though there was no change in ownership. It is likely that the levying of exit will create a cash flow disadvantage for the taxpayer, because there is a cash outflow, but no cash inflow. Moreover, the South African exit tax provisions require that exit tax is paid immediately upon emigration. The “immediate recovery” method of exit tax has raised a number of questions regarding the proportionality vis-à-vis the legitimate purpose of exit tax. Derived from Adam Smith’s first maxim, a tax is considered to be proportional to its purpose if the content and form of the tax does not go beyond what is required to attain the purpose of the tax. This principle is commonly known as the principle of proportionality. Proportionality is also one of the fundamental principles in the European Union ('EU’) and has featured in a number of European court cases concerning exit tax. This minor dissertation seeks to analyse the current legislated exit tax provisions for South Africa and evaluates whether these provisions are proportional to the purpose of exit tax or goes beyond what is necessary to achieve its purpose. The key findings arising from the research presented in this minor dissertation is that an exit tax regime which require an emigrating individual to immediately pay exit tax upon departure may restrict the mobility of that individual and prevent him/her from relocating to another tax jurisdiction. This dissertation found that such a restriction is not proportional to the purpose of exit tax. The mere imposition of exit tax may be justifiable and that it is not so much the principle of levying exit tax that cause concern, but more the timing and method of the application of exit tax. In South Africa, exit tax is due immediately upon departure. In line with the key findings in this dissertation, the current legislated exit tax provisions for South Africa is not proportional to the purpose of such provisions. Other countries have already addressed this issue by implementing alternative measures to levy and collect exit tax which is less burdensome for the taxpayer and therefore considered to be proportional to the purpose of exit tax. One such method is the deferral of exit tax until the point of actual realisation of the accrued gains. Following the analysis as described above, this dissertation finally evaluates the effectiveness of the current legal framework for information exchange and assistance in tax collection in a South African context in order to determine whether the adoption of a method whereby exit tax is deferred and collected upon actual disposal of the asset, is viable in South Africa. This evaluation found that South Africa already have the appropriate legal mechanisms in place in order to collect exit tax debt from a former resident.